Wage-setting policies, employment, and food insecurity: A multilevel analysis of 492,078 people in 139 countries - Reeves, A; Loopstra, R; Tarasuk, V (American Public Health Association, 2021)
Objectives: To examine the association between wage-setting policy and food insecurity.